Pendidikan Akhlak Dalam Kitab Adab An-Nufus dan Ayyuha Al-Walad (Studi Perbandingan Al-Haris Al-Muhasibi dan Abu Hamid Al-Gazali) - Nur Salmah; Mohammad Al Farabi; Azizah Hanum OK (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
The study aims to analyze the moral education perspective of al-??ri al-Mu??sib? in the books ?dab an-Nuf?s and Ab? ??mid al-Gaz?l? in Ayyuh? al-Walad, and to analyse the relevance of moral education perspectives al-H?ri el-Mu??sibí and Abû ?amid al?Gazal? dalm in the kekinian context. This type of research is qualitative research with a library study approach (library research). Data analysis techniques using content analysis techniques. In the book of Adab an-Nuf?s there are 25 thoughts of moral education: to fear God, to be grateful, to believe, and to be honest, to control Lisan, to have a clean heart, to feel vigilant, to avoid evil deeds, to forgive the wrongs of people, to purify oneself from the wrongdoing, to consider the world and the test and trial, to do good to others, to introspect oneself of the wrong and to connect oneself with God, and the 25 ideas of Ab? ??mid al-Gaz?l? in Ayy?h al-Walad are: to be strictly obedient, to observe the counsel received from anyone. Al-H?ri al-Mu??sib? and Ab? ??mid al-Gaz?l? comparisons on moral education are reviewed from three types of morality: morality toward God, toward oneself, and morality towards humans.